2016
DOI: 10.1159/000448682
|View full text |Cite
|
Sign up to set email alerts
|

Argon Preconditioning Protects Airway Epithelial Cells against Hydrogen Peroxide-Induced Oxidative Stress

Abstract: Background: Oxidative stress is the predominant pathogenic mechanism of ischaemia-reperfusion (IR) injury. The noble gas argon has been shown to alleviate oxidative stress-related myocardial and cerebral injury. The risk of lung IR injury is increased in some major surgeries, reducing clinical outcome. However, no study has examined the lung-protective efficacy of argon preconditioning. The present study investigated the protective effects of argon preconditioning on airway epithelial cells exposed to hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…3221-20). Twenty-four hours after plating adherent cells were transferred to custom-made boxes [as described in Hafner et al (2016)] and exposed to four different O 2 conditions supplied by premixed gas bottles: (1) 21% O 2 – 5% CO 2 – 74% N 2 ; (2) 0% O 2 – 5% CO 2 – 95% N 2 ; (3) 10% O 2 – 5% CO 2 – 85% N 2 ; (4) 0–21% O 2 oscillations – 5% CO 2 – rest N 2 with a frequency of six oscillations per hour [as described in Wu et al (2016)]. Analysis of cell responses was performed after 4, 24, and 72 h of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…3221-20). Twenty-four hours after plating adherent cells were transferred to custom-made boxes [as described in Hafner et al (2016)] and exposed to four different O 2 conditions supplied by premixed gas bottles: (1) 21% O 2 – 5% CO 2 – 74% N 2 ; (2) 0% O 2 – 5% CO 2 – 95% N 2 ; (3) 10% O 2 – 5% CO 2 – 85% N 2 ; (4) 0–21% O 2 oscillations – 5% CO 2 – rest N 2 with a frequency of six oscillations per hour [as described in Wu et al (2016)]. Analysis of cell responses was performed after 4, 24, and 72 h of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-four preclinical studies were found. [31213141516171819202122232425262728293031323334353637383940414243444546474849505152] The majority ( n = 25) of in vitro and in vivo studies with Ar focused on neuroprotection after a variety of brain damages,[12131415162022242526272829303133343536373839404149] in which different neurological and behavioral tests were combined with histological and biochemical assays. Four studies evaluated the presence of cardioprotective effect after myocardial ischemia/reperfusion (I/R).…”
Section: Methodsmentioning
confidence: 99%
“…[13171845] Nine studies focused on the preservation of other organs and tissues, such as ex vivo perfused kidney and lung, and culture of human airway epithelium, kidney tubular, and osteosarcoma cells. [192123324647485253] A single study evaluated the influence of Ar inhalation on liver regeneration after partial hepatectomy. [53] Three in vivo studies investigated the effects and the mechanisms of action of Ar under hyperbaric condition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations